Stop pretending what happened when my big sister went crazy - Sones, Sonya (New York : HarperCollinsPublishers, 1999)
A younger sister has a difficult time adjusting to life after her older sister has a mental breakdown.
A novel.
NP
Accelerated Reader AR
Keywords: Mental illness -- Fiction; Sisters -- Fiction; Family -- Fiction; Mental illness -- Fiction; Sisters -- Fiction; Family problems -- Fiction